Intersection of Exegesis on Q.S Al-Waqiah 71-74: Religious Discourse in ‎the Spiritual Paradigm - Nur Muhammad Fatih Al-Badri; Nur Fitriyana; Lukman Nul Hakim (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Humans are faced with multidimensional challenges that include moral and ecological crises, rapid social change, social injustice, rapid technological change and globalization Spiritual challenges in the contemporary era include materialism, consumerism, secularism, technological advancement, pluralism, intolerance, division of Muslim groups related to deviations from Islamic teachings. This often affects a person's spiritual values and religious beliefs. Therefore, this research is important and aims to describe the Intersection of Tafsir Q.S Al-Waqi'ah 71-74: Religious Discourse in the Spiritual Paradigm. This type of research is a literature review with a synergistic approach to three forms of spiritualism paradigms: behavior-based spiritualism, nature-based spiritualism, and religion-based spiritualism. The method used is the maudhu'i method. The primary source of data is the Qur'an. Secondary data sources are tafsir books and several scientific writings relevant to the problem being studied. This research yields a finding that by utilizing the three forms of spiritualism paradigm in synergy —namely, behavior-based spiritualism, nature-based spiritualism, and religion-based spiritualism —it can be understood that the intersection between Q.S. Al-Waqi'ah 71-74 offers a deep insight into the meaning of fire as a symbol of life. Fire is not only a physical need, but also has a spiritual dimension that can lead humans to live a meaningful life, understand the existence of their roles and responsibilities as human beings and the relationship between Allah, fellow humans and nature so as to achieve spiritual happiness by always praying to Him.